C# 8 and .NET Core 3 Projects Using Azure : Build professional desktop, mobile, and web applications that meet modern software requirements, 2nd Edition /: Build professional desktop, mobile, and web applications that meet modern software requirements, 2nd Edition. (2019) - Michaels, Paul; Strauss, Dirk; Rademeyer, Jas
No abstract available